2012
DOI: 10.1089/hum.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Retinitis Pigmentosa Caused by MFRP Mutations: Human Phenotype and Preliminary Proof of Concept

Abstract: Autosomal recessive retinitis pigmentosa (RP), a heterogeneous group of degenerations of the retina, can be due to mutations in the MFRP (membrane-type frizzled-related protein) gene. A patient with RP with MFRP mutations, one of which is novel and the first splice site mutation reported, was characterized by noninvasive retinal and visual studies. The phenotype, albeit complex, suggested that this retinal degeneration may be a candidate for gene-based therapy. Proof-of-concept studies were performed in the rd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…These results demonstrate that injection of an rAAV8(Y733F) vector does not, per se, have any apparent effect on Tg(RHO P347S) PRs, and that the injection wound itself does not enhance PR survival. These findings also support the use of an uninjected eye as an appropriate control, as has been demonstrated by others (38)(39)(40).…”
Section: Pr Expression Of the Raav8(y733f)-hgrk1-stat3-flag Vector Insupporting
confidence: 88%
“…These results demonstrate that injection of an rAAV8(Y733F) vector does not, per se, have any apparent effect on Tg(RHO P347S) PRs, and that the injection wound itself does not enhance PR survival. These findings also support the use of an uninjected eye as an appropriate control, as has been demonstrated by others (38)(39)(40).…”
Section: Pr Expression Of the Raav8(y733f)-hgrk1-stat3-flag Vector Insupporting
confidence: 88%
“…A recent report by Dinculescu et al. (2012) suggested that the retinal dystrophy in MFRP mutations might be a target for gene‐based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, funduscopic analysis and postmortem retinal morphology of vector-injected eyes were normal as compared to the controls (Conlon et al, 2013). Subretinal administration of AAV expressing the wild-type mouse Mfrp (membrane-type frizzledrelated protein) gene prevented retinal degeneration in the Rd6 Mfrp mutant mouse model of autosomal recessive RP (Dinculescu et al, 2012). CNGB1a (subunit of rod cyclic nucleotide-gated (CNG) channel) gene replacement via subretinal space AAV delivery restored the rod CNG channel expression and localization, improving retinal function and vision-guided behavior, and delaying retinal degeneration in autosomal recessive RP mouse model CNGB1 À/À (Koch et al, 2012).…”
Section: Viral-mediated Therapiesmentioning
confidence: 94%